The Role of History Learning in Instilling Nationalism Character Values at SDN Kasomalang VIII - Siti Hulfah; Nurfitria; Endah Robiatul Adawiyah (Indonesian Journal of Educational Science and Technology, 2022)
Instilling the values of nationalism in learning history is very important to be applied in this era of globalization. Instilling the value of nationalism can be an example to form a national character that is in accordance with national identity. Character education is an effort made by the school to shape, direct and guide the behavior of students in accordance with values originating from certain norms to overcome negative impacts in the era of globalization. One of the negative impacts is that the interest of the younger generation in their own culture begins to fade and results in a shift in values in both personal and social life. The influence of historical education on nationalism can have a significant and positive effect on students' historical education on students' nationalism. This means that the attitude of nationalism can be explained and influenced by historical education, learning history provides material on nationalist values so that students are able to understand these values, this shows the large role of historical education in the formation of nationalism among students.